Creativity formation as the basis for development of intellectual potential of economic systems - Козьмук, Наталя Ігорівна; Кліпкова, Оксана Ігорівна (Technology audit and production reserves, 2016)
The concept of creativity is studied in the article as the ability to be creative in terms of cognitive and behavioral characteristics of individuals and a factor of forming intellectual potential of the enterprise. Special attention to the concept of individual creativity is determined by the stage of generating ideas about formation of intellectual property. Generating ideas appears as an "ideas funnel", which clearly reflects the generation, identification and evaluation of ideas. Factors of creative thinking that lead to the generation of ideas are identified. Attention is focused on basic concepts of heuristics science that studies the artistic and creative thinking. Models of ideas selection techniques for their generation in terms of statistics and expert opinion are given. Graphical relationship between the number of generated ideas and the value of spending on the process of identification and generation is shown as the final stage of research.